Efficient Non-Viral Integration and Stable Gene Expression in Multipotent Adult Progenitor Cells - Andrew Wilber; Fernando Ulloa Montoya; Luke Hammer; Branden S. Moriarity; Aron M. Geurts; David A. Largaespada; Catherine M. Verfaillie; R. Scott McIvor; Uma Lakshmipathy (Stem Cells International)
Non-viral integrating systems, PhiC31 phage integrase (ϕC31), and Sleeping Beauty transposase (SB), provide an effective method for ex vivo gene delivery into cells. Here, we used a plasmid-encoding GFP and neomycin phosphotransferase along with recognition sequences for both ϕC31 and SB integrating systems to demonstrate that both systems effectively mediated integration in cultured human fibroblasts and in rat multipotent adult progenitor cells (rMAPC). Southern blot analysis of G418-resistant rMAPC clones showed a 2-fold higher number of SB-mediated insertions per clone compared to ϕC31. Sequence identification of chromosomal junction sites indicated a random profile for SB-mediated integrants and a more restricted profile for ϕC31 integrants. Transgenic rMAPC generated with both systems maintained their ability to differentiate into liver and endothelium albeit with marked attenuation of GFP expression. We conclude that both SB and ϕC31 are effective non-viral integrating systems for genetic engineering of MAPC in basic studies of stem cell biology.